On the strategic importance of developing scientific and technical cooperation among BRICS members - Y. S. Matkovskaya (Стратегические решения и риск-менеджмент)
The author examined the strategic importance and promising areas for the development of scientific and technical cooperation (STC) among the BRICS (and BRICS+) countries. The emergence of the New World Order (NWO) has created conditions for the expansion cooperation among the BRICS members, and the development and, in particular, deepening of the scientific and technical cooperation among the BRICS countries (BRICS+) should make it possible to create a sustainable strategic basis for the development of all BRICS members (and BRICS as a whole). The most important condition for the development of the international STC is the existence of innovative technological and scientific technical potential in the participating countries. Their study allowed the author to establish: 1) their presence in the BRICS countries; 2) the presence of interest of all BRICS countries in the development of STC and in the development of STC with Russia; 3) that the pace of development of STC of the BRICS countries is significantly inferior to the pace of trade and economic cooperation; 3) the presence of both intergovernmental documents and facts of implementation of joint events and programmes in the field of academic and university science, in the field of education. The directions for the development of the BRICS S&T cooperation agreed upon by the participating countries so far should be considered as justified, but it is advisable to develop and deepen them, especially in the direction of environmental protection and in response to the digital transformations taking place in the modern economy. However, for the development of the STC of the BRICS members, it is necessary to define the strategic significance and formulate the principles of understanding the strategic significance of the implementation of the ISTC at this stage of development of science, technology and economy, which is important for almost all BRICS members. For this purpose, the author has formulated the main points that determine the decisions that need to be made, including those related to the assumption of relevant risks, and has first recorded the stages of development of the STC of the BRICS members. The author also suggests considering the possibility of creating cross-border inter-firm innovation ecosystems. In conclusion, it is emphasised that the formation of the strategy of the STC of the BRICS members requires respect for their interests and the use of an ecosystem approach and fine-tuning.